Meningkatkan Hasil Belajar Peserta Didik melalui Penerapan Model Number Head Together di Kelas VII 5 SMPN 33 Palembang - Anggun Novtaria; Umi Chotimah; Nyimas Nuria Hasna Anggraeni (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research was conducted to improve the quality of researchers as prospective young teachers regarding the problem of learning outcomes in class VII SMP so that the author took the initiative to carry out the learning process through the number head Together model. Continuous development becomes a reference for self-improvement through an independent curriculum. This research was conducted based on the discovery of problems when carrying out learning, namely students who were less active and varying student abilities causing low learning outcomes. The number head together learning model is needed as an effort to increase student activity which can add new understanding to students. This research was conducted using classroom action research using data collection techniques through observation, tests and documentation. The research results showed that there was an increase in the percentage of student learning outcomes in pre-cycle activities, increasing from 36.66% to 76.66 in cycle 1 and 83.33% in cycle 2. This research was assisted by the application of the TaRL approach. So that the classroom action research carried out was successful.